Constitution, democracy, regulation of the internet and electoral fake news in Brazilian elections | Constituição, democracia, regulação da internet e fake news nas eleições brasileiras - Campinho, Bernardo Brasil (Revista Publicum, 2019)
Abstract: In the last general election held in Brazil, Laura Chinchilla, a representative of the Organization of American States (OAS) observer mission, considered the massive use of fake news through social networks, notably WhatsApp, an "unprecedented" phenomenon. The phrase registers a state of novelty and, at the same time, uncertainty in the legal and social scenario of the Brazilian democracy, which since 1996 has strongly invested in the computerization of the electoral process and has specifically regulated the phenomenon of Internet use in the electoral process. Thus, a great question arises about the role that the advances of the digital world, more specifically the Internet and social networks, can play in defining the democratic agenda, especially when they place on the one hand democratic legitimacy and respect for human rights and on the other the extent of economic and social power (including its abuse) enhanced by individuals and groups through new digital technologies. In this way, this work seeks to analyze the legal frameworks for the use of the Internet in the Brazilian elections and how the existing normativity responds to the fake news phenomenon and its implications for the full realization of constitutional democracy. In order to do so, the paper proposes a comparison between the existing legislation in Brazil on electoral use of the Internet and its appropriation and effectiveness (or absence thereof) in decisions of the Brazilian electoral courts, including the Superior Electoral Court, seeking to understand how the established dialogue between norms and judicial decisions reflects more or less effectiveness of the existing regulation for the use of the Internet and social networks in the elections, delimiting if the degree of effectiveness presented accomplishes or frustrates the constitutional bases of democracy in Brazil. Resumo: Nas últimas eleições gerais realizadas no Brasil, Laura Chinchilla, representante da missão de observação da Organização dos Estados Americanos (OEA), considerou o uso massivo de notícias falsas (fake news) por meio de redes sociais, notadamente o WhatsApp, um fenômeno "sem precedentes". A declaração registra um estado de novidade e, ao mesmo tempo, incerteza no cenário jurídico e social da democracia brasileira, que desde 1996 investe fortemente na informatização do processo eleitoral e regulou especificamente o fenômeno do uso da Internet no mundo. Assim, surge uma grande questão sobre o papel que os avanços do mundo digital, mais especificamente a Internet e as redes sociais, podem desempenhar na definição da agenda democrática, especialmente quando colocam, por um lado, a legitimidade democrática e o respeito aos direitos humanos e, por outro, a extensão do poder econômico e social decorrente da internet e das redes sociais (incluindo a possibilidade de seu abuso) por indivíduos e grupos. Dessa forma, este trabalho busca analisar os marcos legais para o uso da Internet nas eleições brasileiras e como a normatividade existente responde ao fenômeno das notícias falsas (fake news) e suas implicações para a plena realização da democracia constitucional. Para tanto, o artigo propõe uma comparação entre a legislação existente no Brasil sobre uso eleitoral da Internet e sua apropriação e efetividade (ou ausência dela) nas decisões dos tribunais eleitorais brasileiros, incluindo o Tribunal Superior Eleitoral, buscando entender como o diálogo estabelecido entre normas e decisões judiciais reflete mais ou menos efetividade da regulamentação existente para o uso da Internet e redes sociais nas eleições, delimitando se o grau de efetividade apresentado realiza ou frustra as bases constitucionais da democracia no Brasil.